Understanding voriconazole metabolism: a middle-out physiologically-based pharmacokinetic modelling framework integrating in vitro and clinical insights - Saleh, Ayatallah; Schulz, Josefine; Schlender, Jan-Frederik; Aulin, Linda B. S.; Konrad, Amrei-Pauline; Kluwe, Franziska; Mikus, Gerd; Huisinga, Wilhelm; Kloft, Charlotte; Michelet, Robin (Clinical pharmacokinetics, 2024)
Voriconazole (VRC), a broad-spectrum antifungal drug, exhibits nonlinear pharmacokinetics (PK) due to saturable metabolic processes, autoinhibition and metabolite-mediated inhibition on their own formation. VRC PK is also characterised by high inter- and intraindividual variability, primarily associated with cytochrome P450 (CYP) 2C19 genetic polymorphism. Additionally, recent in vitro findings indicate that VRC main metabolites, voriconazole N-oxide (NO) and hydroxyvoriconazole (OHVRC), inhibit CYP enzymes responsible for VRC metabolism, adding to its PK variability. This variability poses a significant risk of therapeutic failure or adverse events, which are major challenges in VRC therapy. Understanding the underlying processes and sources of these variabilities is essential for safe and effective therapy. This work aimed to develop a whole-body physiologically-based pharmacokinetic (PBPK) modelling framework that elucidates the complex metabolism of VRC and the impact of its metabolites, NO and OHVRC, on the PK of the parent, leveraging both in vitro and in vivo clinical data in a middle-out approach.
Gesehen am 09.04.2025